1997
DOI: 10.1042/cs0930435
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular Hypertension with Low-to-Normal Plasma Renin: Clinical and Angiographic Features

Abstract: 1. Low-to-normal renin renovascular hypertension (RVH) and the accuracy of renal vein renin ratios were investigated in 129 consecutive patients referred for suspected RVH. Forty-nine had essential hypertension, 24 unilateral renoparenchymal hypertension and 56 renal artery obstruction. Of the latter, 86% were diagnosed retrospectively as RVH, based on fall in blood pressure with correction of renal ischaemia. We measured baseline, captopril-stimulated and renal vein plasma renin activity (PRA) levels, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…However, some limitations of this study should be recognized. Previous clinical studies reported normal plasma renin activity (PRA) levels in 25%-37% of patients with RVD 35,36 (suggesting PRA as an unreliable index of RVD 37 ), whereas the swine model show an early but transient increase that goes back to baseline levels after 4-6 weeks of RVD. 10,38 Because of the growth pattern and size limitations, the animals used in the study are relatively young and consequently, lack some common comorbid diseases often observed associated with human CKD, such as obesity 39,40 or diabetes, 41 that may compromise renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some limitations of this study should be recognized. Previous clinical studies reported normal plasma renin activity (PRA) levels in 25%-37% of patients with RVD 35,36 (suggesting PRA as an unreliable index of RVD 37 ), whereas the swine model show an early but transient increase that goes back to baseline levels after 4-6 weeks of RVD. 10,38 Because of the growth pattern and size limitations, the animals used in the study are relatively young and consequently, lack some common comorbid diseases often observed associated with human CKD, such as obesity 39,40 or diabetes, 41 that may compromise renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma renin activity was measured by a commercially available kit (Ares Serono, Milan, Italy, supine normal values with a daily sodium intake of 100 to 200 mmol: 0.51 to 2.64 ng Ang I ⅐ mL Ϫ1 ⅐ h Ϫ1 ) as reported. 17 PAI-1:Ag levels were assayed by an ELISA method (TintElize PAI-1, Biopool, Umeå, Sweden) following the manufacturer's protocols 18 (normal range 4 to 30 ng/mL). The within and between assay coefficients of variation of this assay were 1.9% and 2.4%, respectively.…”
Section: Blood Sampling and Biochemical Measurementsmentioning
confidence: 99%
“…In the majority of studies concerning adults, a lack of sensitivity and specificity of RVR ratios in predicting cure following surgery has been reported [15,16], especially in the presence of low-to-normal plasma renin [17]. The correlation between the arteriographic appearance and functional significance of renal artery stenosis has been poor in adults, perhaps due to the non-linear relationship between the anatomical degree of stenosis and its functional effects on flow and pressure distal to the stenosis [18,19].…”
Section: Introductionmentioning
confidence: 91%
“…The correlation between the arteriographic appearance and functional significance of renal artery stenosis has been poor in adults, perhaps due to the non-linear relationship between the anatomical degree of stenosis and its functional effects on flow and pressure distal to the stenosis [18,19]. Low values of peripheral renin, technical errors, bilateral disease, segmental artery involvement, and coexisting functionally unimportant renal artery stenosis in angiograms of patients with mainly essential hypertension contribute to its poor specificity [3,17,20,21,22]. In this retrospective study, we have assessed 25 years of our experience and, in particular, the association between RVR ratios and the subsequent outcome, with or without surgery/angioplasty, in hypertensive children.…”
Section: Introductionmentioning
confidence: 98%